1998
DOI: 10.1074/jbc.273.19.11483
|View full text |Cite
|
Sign up to set email alerts
|

Cell Surface Glycosaminoglycans Do Not Serve as Ligands for PECAM-1

Abstract: Previous studies have suggested that PECAM-1 mediates cellular interactions via both homophilic and heterophilic adhesive mechanisms. Cell surface glycoaminoglycans have been implicated as one of the heterophilic ligands for PECAM-1. To determine whether PECAM-1 is capable of interacting directly with glycosaminoglycans, we examined the adhesive properties of multiple monovalent and multivalent forms of this adhesion molecule. We found that the binding of a bivalent PECAM-1/IgG chimeric protein or multivalent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 46 publications
(37 reference statements)
0
23
0
Order By: Relevance
“…These experiments illustrate that specificity must be controlled in binding studies using recombinant protein/human IgG1 Fc chimeras. In fact, nonspecific binding of PECAM-1/Fc chimeras was noted in an early study by Sun et al (26), and the potential for nonspecific binding of Fc chimeras to FcRs was noted in a recent study by Stark et al (14).…”
Section: Discussionmentioning
confidence: 99%
“…These experiments illustrate that specificity must be controlled in binding studies using recombinant protein/human IgG1 Fc chimeras. In fact, nonspecific binding of PECAM-1/Fc chimeras was noted in an early study by Sun et al (26), and the potential for nonspecific binding of Fc chimeras to FcRs was noted in a recent study by Stark et al (14).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that PECAM-1-dependent heterophilic ligand interactions 2,6 with constituents of the extracellular matrix may be involved in the stimulation of filopodia formation by PECAM-1, although the existence of these interactions has been questioned. 4 Small GTPases of the Rho superfamily (RhoA, Rac1, and Cdc42) have been linked to actin cytoskeletal remodeling and morphological changes involved in cell motility, with Cdc42 implicated in the formation of filopodia. [31][32][33][34][35] Our data indicating that the protein levels of Cdc42 are increased in cells expressing PECAM-1 ( Figure 9) are therefore consistent with a role for PECAM-1 in the formation of filopodia.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] To determine whether PECAM-1-dependent ligand interactions might play a role in the ability of PECAM-1 to promote endothelial filopodia formation, we studied the effects of two functionally distinct antibodies: mAb 37, which blocks heterophilic binding; and mAb 62, which blocks both homophilic and heterophilic bindings. 49 We found that the initial formation of filopodia by HUVEC was suppressed by both antibodies but not by control IgG (Table 1).…”
Section: Anti-pecam-1 Antibodies Inhibit Filopodia Formation By Huvecmentioning
confidence: 99%
See 1 more Smart Citation
“…mAb Gi18 directed against the first two domains of PECAM-1 was produced and characterized in our laboratory (29). mAbs PECAM 1.1 and PECAM 1.2 recognizing domains 5 and 6 of PECAM-1, respectively, have been previously described (24,30). mAbs 68-5H11 and AK-4 against E-and P-selectin, respectively, were purchased from BD Pharmingen (Heidelberg, Germany).…”
Section: Methodsmentioning
confidence: 99%